Malaysian anti corruption commission: another propaganda / Mohamad Siddiq Mohd Azani … [et al.] - Mohd Azani, Mohamad Siddiq; Yahya, Mohd Fadhli; Zaidon, Ahmad Ziadi; Naibmuddin, Norsyafiqah (2009)
This research is a study on the establishment of the Malaysian Anti Corruption Commission (MACC). The problem of corruption must be given a wide attention as it had become a huge problem nowadays. The new establishment of MACC is said to replace the Anti Corruption Agency (ACA). It is said that the MACC is more effective in combating corruption due to it independent and transparent status. MACC is also established in accordance to the successful body of Independent Commission Against Corruption of Hong Kong (ICAC). The reason for this research is to look at the jurisdiction of this newly established commission. It is to see whether the commission is just propaganda. Based on the research done, it was found that MACC is not really independent as it is still depending on the Act and Public Service Commission. For the effectiveness and the impartiality of this commission, it is still early to say as MACC do prosecutes from both governing and opposition party but it is still early to be judged as most are the cases are still not yet being decided.